A compensação como meio hábil à extinção concomitante de obrigações tributárias contrapostas - Oliveira, Flávia Cecília de Souza (2009)
This work aims the study of tax offsetting so as to concomitantly extinguish the existing credit relation between Tax Administration and taxpayer and the existing credit relation between taxpayer and Tax Administration. Initially, the constitutional aspects, which regulate the principle, were briefly analyzed and, then, proceeded to an infra-constitutional examination. The study is restricted to tax offsetting, which the Federal Government is competent to establish in accordance with the Constitution of the Republic. The justification to select the theme regards the fact that offsetting is currently an effective mean to extinguish both the taxpayer debt relation before the Tax Administration and the latter debt relation in regard to taxpayer. We will analyze the essential elements of the origin of the right to offset and, further approach the general characteristics, considering the Law and principles systematic analysis, specially, Law General Theory, Constitutional Law, Civil Law, Civil Procedural Law, Tax Law, Tax Procedural Law and Administrative Law. We will also examine some pragmatic aspects that comprise the principle under analysis, specially the standing adopted by the Taxpayers Council, within the ambit of administrative proceedings, as well as that of Superior Court of Justice, within the ambit of legal proceedings. Further to constitutional, legal, doctrinal and jurisprudence analysis of the matter, we will present our findings in regard to some specific themes in connection with the object hereof